Response of Human Mesenchymal Stromal Cells from Periodontal Tissue to LPS Depends on the Purity but Not on the LPS Source. (2nd July 2020) - Behm, Christian; Blufstein, Alice; Abhari, Setareh Younes; Koch, Christoph; Gahn, Johannes; Schäffer, Christina; Moritz, Andreas; Rausch-Fan, Xiaohui; Andrukhov, Oleh
Abstract : Human periodontal ligament stromal cells (hPDLSCs) and gingival mesenchymal stromal cells (hGMSCs) are resident mesenchymal stromal cells (MSCs) of the periodontal tissue. The lipopolysaccharide (LPS) from Porphyromonas gingivalis is structurally distinct from that of other Gram-negative bacteria, and earlier studies linked this structural difference to a distinct virulence activity and the ability to activate toll-like receptor 2 (TLR-2), besides TLR-4 as commonly occurring upon LPS challenge. Later studies, in contrast, argue that TLR-2 activation by P. gingivalis LPS is due to lipoprotein contamination. In the present study, we aimed to define the influence of structure versus purity of P. gingivalis LPS on the immune response of hPDLSCs and hGMSCs. Cells were stimulated with commercially available "standard" P. gingivalis LPS, "ultrapure" P. gingivalis LPS, or "ultrapure" Escherichia coli LPS, and the expression of interleukin- (IL-) 8, IL-6, monocyte chemoattractant protein- (MCP-) 1, TLR-2, and TLR-4 was evaluated. The contribution of TLR-4 to the LPS-induced response was assessed using the specific TLR-4 inhibitor TAK-242. "Standard" P. gingivalis LPS induced significantly higher IL-8, IL-6, and MCP-1 production compared to the "ultrapure" LPS preparations, with no significant difference detectable for "ultrapure" LPS from P. gingivalis and E. coli . By using TAK-242, the response of hPDLSCs and hGMSCs to "ultrapure" LPS preparations was effectively inhibited to the levels comparable to those of nonstimulated controls. In contrast, high levels of response to "standard" LPS were observed, even in the presence of TAK-242. Our data show that the response of MSCs from periodontal tissue to LPS depends more on the purity of the LPS preparation than on the LPS source. Even a small amount of contaminating lipoproteins can drastically enhance the hPDLSCs' and hGMSCs; responsiveness to P. gingivalis LPS, which might also contribute to the progression of periodontal disease.